Historical reflections on Sámi art and the paradigm of the National in Norwegian art history. - Grini, Monica (Orkana forlag, 2014)
Whose story is told in the history of art? There are many different answers to that question depending on which art history one refers to and on the perspective applied to examine these histories. One approach is to look at the traditional framework for such examinations – which to a large degree still includes categories such as state, place and nation. Sápmi, the Sámi area, can be understood as a nation embracing four nation-‐states: Norway, Sweden, Finland and Russia. Since the 19th century, the history of art has been considered part of the nation-‐ state’s inventory. The production of art history has played, and still plays, a role in the constitution and the maintenance of different nation-‐states. How is Sámi art presented in Norwegian art history and what are the roles of the national paradigm in this presentation?